PENINGKATAN KOMPETENSI SISWA MAN KOTA SURABAYA MELALUI PELATIHAN DASAR PERANCANGAN SISTEM APLIKASI MOBILE - Titik Lusiani; Didiet Anindita Arnandy; A.B. Tjandrarini; Nunuk Wahyuningtyas; Edo Yonatan Koentjoro (Jurnal Abdi Insani, 2026)
The rapid development of digital technology requires young generations, particularly Madrasah Aliyah students, to possess adequate skills and understanding in information technology. However, many students at MAN Kota Surabaya still lack sufficient knowledge of the fundamental concepts of mobile application system design, which are essential to face challenges and opportunities in the digital era. This training activity aimed to provide initial knowledge and skills in developing mobile applications and to specifically enhance students’ competencies in understanding the basics of system design. The program was conducted through interactive training combining lectures and hands-on practice. The training materials covered an introduction to application systems and requirements analysis, business process design, database design, and UI/UX design. The activity was held at MAN Kota Surabaya on July 15, 2025, involving 34 students. The results indicated a significant improvement in students’ understanding of basic mobile application system design. Evaluation using pre-tests and post-tests showed increased enthusiasm and learning motivation due to the use of case-based training methods. The average pre-test score of 76 increased to 93 in the post-test, representing an improvement of 17 points. Detailed results showed score increases of 1 point in meeting one, 35 points in meeting two, 24 points in meeting three, and 9 points in meeting four. In conclusion, the training not only provided practical skills but also fostered students’ motivation to continuously develop their competencies in information technology.